Behavior and flow mechanism of shock train self-excited oscillation influenced by background waves. (January 2020) - Hou, Wenxin; Chang, Juntao; Xie, Zongqi; Wang, Youyin; Wu, Linke; Bao, Wen
Abstract: This study investigates shock train self-excited oscillation—influenced by background waves—occurring within an isolator in a direct-connect wind tunnel. The experimental data were obtained using high-speed Schlieren technique and high-frequency pressure measurements. Three oscillation modes of shock train self-excited oscillations were studied and have been presented in detail. These include Top-Large-Separation, Bottom-Large-Separation, and transition modes. The observed shock train with background waves conformed to one of the three modes, whereas the oscillation mode appeared randomly within a uniform incoming flow. To understand the differences of shock train unsteady behaviors in different modes, the distributions of intermittent region and zero-crossing frequency were compared. Furthermore, the mode and approximate location of the oscillations were judged by the distribution of wall pressure standard deviation. The influence of background waves on the shock train self-excited oscillation was then analyzed. For the shock train in a uniform incoming flow, the Strouhal number always lies in the range of 0.01–0.03, and the Strouhal number at both side walls is substantially equal. However, for the shock train influenced by background waves, the Strouhal number may fall outside the range of 0.01–0.03, and Strouhal number at the top and bottom walls is different. It was found that the wall pressure gradient caused by background waves affects the instability in the separation zone after the shock train leading edge, thereby influencing the unsteadiness of shock train self-excited oscillation. Highlights: Three oscillation modes of shock train self-excited oscillation influenced by background waves were studied. The differences between self-excited oscillation in a flow with background waves and in a uniform flow were discussed. The influence mechanism of background waves on shock train self-excited oscillation was revealed.